2012 Millennialism Becomes Conspiracist Teleology: Overlapping Alternatives in the Late Twentieth Century Cultic Milieu - Whitesides, Kevin A. (Nova religio, 2015)
Due to shared conceptions of the degeneracy of the modern era and a common distrust of mainstream narratives, New Age and conspiratorial milieus have often cross-fertilized. Conspiracy narratives can provide accounts of the types of corruption to be remedied by the advent of the next world age, and prophetic narratives of a new age can provide a teleological focus for the eventual success or defeat of the conspiracy. New Age interest in the millenarian significance of the Maya Long Count calendar took hold in the 1970s as an array of expectations for an approaching golden age around the year 2012. As such expectations became a more well-established commodity in countercultural circles, the associated dates were eventually incorporated into a variety of conspiracy narratives. Each innovator of 2012 conspiracism adapted this dating scheme into his or her own context in a manner that is exemplary of the improvisational style that Michael Barkun noticed to be prevalent in contemporary American conspiracy discourse; “2012” became utilized as a teleological trope which could be incorporated wherever such a temporal focus was desired.